2020
DOI: 10.21203/rs.3.rs-42538/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of HSD11B2 as a prognostic marker in Melanoma via TCGA data mining

Abstract: Background: Hydroxysteroid 11-Beta Dehydrogenase 2 (HSD11B2) expression has been reported to be present in melanoma. We investigated the association of HSD11B2 with melanoma using publicly available data from The Cancer Genome Atlas (TCGA). Methods: The relationship between clinical pathologic features and HSD11B2 were analysed via Wilcoxon signed-rank test and logistic regression. Clinicopathologic characteristics associated with overall survival in melanoma patients were calculated using Cox regression and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…In this study, a total of seven glycolysis-related lncRNAs (AL353804.1, AC010719.1, TNFRSF10A-AS1, AC005586.1, AL355574.1, AC009948.1, and AL161785.1) with prognostic significance in STAD were identified using Lasso and Cox regression analyses. Among them, the two glycolysis-related LncRNAs (TNFRSF10A-AS1 and AC009948.1) have been reported in previous studies (FU et al, 2020;Wei et al, 2020). In a study by Wei et al (Xia et al, 2021), TNFRSF10A-AS1 was identified as an autophagy-related lncRNA associated with the poor prognosis of colorectal cancer, and along with other seven autophagy-related lncRNAs, it constructed a prognostic signature for colorectal cancer, which was used to predict the prognosis in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, a total of seven glycolysis-related lncRNAs (AL353804.1, AC010719.1, TNFRSF10A-AS1, AC005586.1, AL355574.1, AC009948.1, and AL161785.1) with prognostic significance in STAD were identified using Lasso and Cox regression analyses. Among them, the two glycolysis-related LncRNAs (TNFRSF10A-AS1 and AC009948.1) have been reported in previous studies (FU et al, 2020;Wei et al, 2020). In a study by Wei et al (Xia et al, 2021), TNFRSF10A-AS1 was identified as an autophagy-related lncRNA associated with the poor prognosis of colorectal cancer, and along with other seven autophagy-related lncRNAs, it constructed a prognostic signature for colorectal cancer, which was used to predict the prognosis in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 87%
“…These findings also suggested that the TNFRSF10A-AS1 might participate in a variety of biological processes, affecting the prognosis of various tumors, and is worthy of further exploration in subsequent studies with good research potential. Fu et al (FU et al, 2020) found that AC009948.1 was co-expressed with HSD11B2, which is related to the progression and prognosis of melanoma as demonstrated by mining the data of melanoma in TCGA. The GSEA analysis suggested that HSD11B2 was related to multiple cancer-related genes and pathways, including cytosolic DNA-sensing pathway, JAK_STAT signaling pathway, T-cell receptor signaling pathway, and Toll-like receptor signaling pathway.…”
Section: Discussionmentioning
confidence: 96%